Decreased Sulfate Content and Zeta Potential Distinguish Glycosaminoglycans of the Extracellular Matrix of Osteoarthritis Cartilage - Nunes, Rodolfo de Melo; Girão, Virgínia Claudia Carneiro; Cunha, Pablyana Leila Rodrigues; Feitosa, Judith Pessoa Andrade; Pinto, Ana Carolina Matias Dinelly; Rocha, Francisco Airton Castro (Frontiers in Medicine, 2021)
We aimed to determine the characteristics that distinguish glycosaminoglycans (GAGs) from osteoarthritis (OA) and normal cartilage and from men and women. Cartilage samples from 30 patients subjected to total joint arthroplasty secondary to OA or fracture (control) were evaluated, and the GAG content (μg/mg dry cartilage) after proteolysis was determined by densitometry, using agarose-gel electrophoresis. Relative percentages of carbon (C), nitrogen (N), and sulfur (S) in GAGs were determined by elemental microanalysis, as well as the zeta potential. Seventeen samples (56.6%) were from patients >70 years old, with 20 (66.6%) from women, and most [20 (66.6%)] were from the hip. The GAG content was similar regardless of patients being >/≤ 70 years old with 96.5 ± 63.5 and 78.5 ± 38.5 μg/mg (P = 0.1917), respectively. GAG content was higher in women as compared to men, with 89.5 ± 34.3 and 51.8 ± 13.3 μg/mg, respectively (P = 0.0022), as well as in OA than fracture samples, with 98.4 ± 63.5 and 63.6 ± 19.6 μg/mg, respectively (P = 0.0355). The GAG extracted from the cartilage of patients >70 years old had increase in N, and there were no gender differences regarding GAG elemental analysis. GAG from OA had a highly significant (P = 0.0005) decrease in S% (1.79% ± 0.25%), as compared to fracture samples (2.3% ± 0.19%), with an associated and significant (P = 0.0001) reduction of the zeta potential in the OA group. This is the first report of a reduced S content in GAG from OA patients, which is associated with a reduced zeta potential.